Automated diagnostic analysis of ocular fundus photographs - Liu, Zheng. (2008)
The retinal vessels are the only vascular network of human body that can be ob-served directly. The retinal image on the ocular fundus photograph can provide pathological changes caused by some eye diseases such as glaucoma, which may lead to loss of vision. It can also indicate early signs of some systemic diseases such as diabetes and hypertension. As it is important to detect malign changes and ab-normal structures of the retina as early as possible and to monitor their progress during clinical therapy, the development of an automatic retinal image analysis system offers a potential of helping ophthalmologist diagnose retina-related dis-eases, especially during mass screening. In this project, we propose a cost-effective and efficient image analysis system which may provide useful information to the doctor and extend his/her capability and productivity during clinical examination.